1981
DOI: 10.1007/bf00496788
|View full text |Cite
|
Sign up to set email alerts
|

Histology and histochemistry of the accessory reproductive glands in the male hairy-nosed wombat (Lasiorhinus latifrons)

Abstract: The accessory male reproductive glands of the hairy-nosed wombat, Lasiorhinus latifrons, are a prostate and three pairs of Cowper's glands. Component units of all are branched tubular structures of varying epithelial makeup and secretory content. The prostate has the carrotlike shape and three consecutive regions commonly found in marsupials. The regions differ in their tubular histology and histochemistry: all contain secretory globules in glandular lumina. Cowper's glands A and B are histologically identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…Nielsen (22) stated that although the bulbourethral gland of the rat contains sialomucin, sulfated acid mucosubstances are the main constituents and that the presence of sialomucin in the golden hamster is more doubtful. Barbour (1) reported that the wombat has three pairs of the glands, and that the secretion of gland A contains protein but little carbohydrate, that of gland B a neutral glycoprotein and that of gland C a sialomucin. Furthermore, the gland of the horse is serous (4).…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen (22) stated that although the bulbourethral gland of the rat contains sialomucin, sulfated acid mucosubstances are the main constituents and that the presence of sialomucin in the golden hamster is more doubtful. Barbour (1) reported that the wombat has three pairs of the glands, and that the secretion of gland A contains protein but little carbohydrate, that of gland B a neutral glycoprotein and that of gland C a sialomucin. Furthermore, the gland of the horse is serous (4).…”
Section: Discussionmentioning
confidence: 99%
“…While penile spines in other mammals (e.g. felids) are sometimes associated with vaginal or cervical stimulation resulting in induced ovulation, there is currently Owen (1919) CW _ Detailed account of the gross anatomy of the reproductive system \ Full description of the gross urogenital anatomy Pearson (1944) CW \ Description of the gross urogenital anatomy Barnett & Brazenor (1958) CW _ Presence of a rete mirabile in the spermatic cord Hughes (1965) CW _ Sperm morphology Brooks et al (1978) SHNW _ Full description of the reproductive system; structural and biochemical characteristics of accessory reproductive glands; sperm morphology Barbour (1981) SHNW _ Full description of the reproductive system; histology and histochemistry of accessory reproductive glands Gaughwin (1981) SHNW _ Structural and biochemical characteristics of the reproductive organs \ Structural characteristics of the urogenital tract Hughes & Green (1998) CW \ Placentation Moritz et al (1998) CW \ Ovarian and uterine histological changes associated with the oestrous cycle Taggart et al (1998) SHNW _ Seminal characteristics Hamilton et al (2000) SHNW _ Seasonal change in accessory glands (structure) Breed et al (2001) CW _ Sperm morphology (i.e. the structural organisation of sperm head components) MacCallum (2004) CW _ Gross anatomy and testicular histology of the reproductive tract and sperm morphology \ Examined the urogenital system (i.e.…”
Section: Male Gross Anatomymentioning
confidence: 99%
“…The segments of the wombat prostate differ in their cytology, tubular histology and histochemistry, and Barbour (1981)). Prostatic bodies (i.e.…”
Section: Accessory Glandsmentioning
confidence: 99%
See 2 more Smart Citations